A synthesis of qualitative research exploring the barriers to staying in work with chronic musculoskeletal pain - Toye, F; Seers, K; Allcock, N; Briggs, M; Carr, E; Barker, K (Taylor and Francis, 2015)
Purpose: Qualitative research can help to advance our understanding, management and prevention of work disability. Our aim was to integrate qualitative research findings in order to increase our understanding of barriers to stay in work with chronic pain. Methods: We searched five electronic bibliographic databases until September 2012, supplemented by citation tracking and hand-searching. We used meta-ethnography to synthesis our findings. Central to meta-ethnography is identifying “concepts” and developing a conceptual model. Concepts were compared and organised into categories. Results: The following categories can have an impact on the decision to remain in work: struggling to affirm myself as a good worker; balancing life and work in the face of unpredictable symptoms; my work colleagues don't believe me; the system does not facilitate return to work; the battle for legitimacy. Conclusions: Our innovation is to present an internationally relevant model based on a conceptual synthesis. This model highlights the adversarial work experience of people with chronic. The papers span 15 years of qualitative research. A significant finding is that these themes continue to pervade the current work environment for those in pain, and this has clear implications for education, social care and policy.